TIGIT is upregulated by HIV-1 infection and marks a highly functional adaptive and mature subset of natural killer cells - Vendrame, Elena; Seiler, Christof; Ranganath, Thanmayi; Zhao, Nancy Q; Vergara, Rosemary; Alary, Michel; Labbé, Annie Claude; Guédou, Fernand; Poudrier, Johanne; Holmes, Susan; Michel, Roger; Blish, Catherine A (bioRxiv, 2019)
Objective: Our objective was to investigate the mechanisms that govern natural killer (NK) cell responses to HIV, with a focus on specific receptor-ligand interactions involved in HIV recognition by NK cells. Design and Methods: We first performed a mass cytometry-based screen of NK cell receptor expression patterns in healthy controls and HIV+ individuals. We then focused mechanistic studies on the expression and function of T cell immunoreceptor with Ig and ITIM domains (TIGIT). Results: The mass cytometry screen revealed that TIGIT is upregulated on NK cells of untreated HIV+ women, but not in antiretroviral-treated women. TIGIT is an inhibitory receptor that is thought to mark exhausted NK cells; however, blocking TIGIT did not improve anti-HIV NK cell responses. In fact, the TIGIT ligands CD112 and CD155 were not upregulated on CD4+ T cells in vitro or in vivo, providing an explanation for the lack of benefit from TIGIT blockade. TIGIT expression marked a unique subset of NK cells that express significantly higher levels of NK cell activating receptors (DNAM-1, NTB-A, 2B4, CD2) and exhibit a mature/adaptive phenotype (CD57hi, NKG2Chi, LILRB1hi, FcRγlo, Syklo). Furthermore, TIGIT+ NK cells had increased responses to mock-infected and HIV-infected autologous CD4+ T cells, and to PMA/ionomycin, cytokine stimulation and the K562 cancer cell line. Conclusions: TIGIT expression is increased on NK cells from untreated HIV+ individuals. Although TIGIT does not participate directly in NK cell recognition of HIV, it marks a population of mature/adaptive NK cells with increased functional responses.